Student Perceptions about the Implementation of Web Applications During Distance Learning - Muhamad Sofian Hadi; Zaitun Zaitun; Dwi Chika Aprilia (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2021)
This study aimed to obtain data on students' perceptions about the implementation of web applications during distance learning in the Covid 19 pandemic which was held at MAN 22 Jakarta. There were 66 students involved in this study as research respondents and consists of class X Science and X Language. The results of data processing in a percentage of 83.9% which led to student approval of the implementation of web applications during distance learning in MAN 22 Jakarta. The indicators used in this study were the material and media aspects of learning, the interaction in the learning process and the aspects of the learning atmosphere which became the assessment which were then processed using the Likert Scale method by spreading questionnaire through Google form in conducting research in order to obtain students' perceptions.